Utilization of the Integrated School Information System to Optimize the Quality of Financial Management and Implementation of Education at SMK Harum Sentosa Perbaungan Serdang Bedagai - Harumy, T. Henny Febriana; Br.Ginting, Dewi Sartika; Manik, F.Y.; Ridlo, M.R (Talenta Publisher, 2023)
The problems that exist in the partner environment are financial data collection, especially payroll, and the school fee payment system is done manually so that income and expenditure discrepancies often occur. Furthermore, data collection for setting school operational costs is still done manually making it difficult when reporting the BOS budget (school operational assistance), teacher and student attendance systems are ineffective, management system data collection, inventory is still manual so it is not known what inventory items are owned, data collection Unstructured Library Books. The use of information technology that has not been integrated into the learning process. The solution to the problems to be handled is the use of an integrated school information system. Implementation methods used to overcome the problems encountered include; observation, identification of partner problems, solutions to partner problems consisting of: (1) Observation of partners (2) Introduction of integrated school information systems. (3) Assistance in the use of an integrated school information system for the school management team. (4) Training and mentoring for teachers to use teaching material features, E-Absence and Smart Library (5) Evaluation in each implementation of the service program, as well as the outcome targets for service. The results of this Community Service Activity were an increase marked by Based on pre -the test given before the delivery of the material and the post-test carried out by the participants after receiving the material exposure and training found that there was a significant change from the pre-test score with an average value of 1 and 2, namely enough and less to an average value of 3 and 4 with good and very good weight scores when doing the post-test. This shows that the teachers and the management team who participated in the training understood the material presented.